Distribution of Benthic Insect Fauna in a West African Lagoon: The Porto-Novo Lagoon in Benin - ADANDEDJAN, Delphine; LALEYE, Adédjobi Philippe; ALLASSANE, Ouattara; GOURENE, Germain (My University, 2011)
The distribution of aquatic insect fauna of Porto-Nova lagoon was studied through seasonally sampling from July 2007 to June 2008. A total of 52 taxa belonging to 7 orders and 29 families were recorded. The richest taxonomie diversity was observed for Heteroptera, Ephemeroptera and Odonates. Certain species such as Diplonychus sp. (Belostomidae), Chironomus sp., Chironomus formosipennis and Polypedilum fuscipenne (Chironomidae) and Libellulidae (Libellula sp.) were the most constant taxa observed during the sampling period. The distribution pattern observed thanks to the Kohonen map (SOM) is characterized by a rich assemblage and varied from upstream to downstream. The highest specifie diversity (69.29%) was gotten during the law rainy season (October) and the lowest (29.8%), during the high dry season (February). This pattern resulted from the species reproductive process of most insects orders, in relation with a decrease of the rate of the salinity and an increased water temperature. But then, the law rate of species richness recorded during the dry season will be explained by the lacking of efficient recruiting and a strong predation during this period. Besicles, hydrological factors and human activities could be also the important factors of controlling the distribution of this fauna. The invasion of the lagoon by the floating vegetation can be advanced as a factor of forçage of the temporal variations of the organisms.
Keywords: Insects fauna; distribution; SOM; lagoon; Porto-Novo